Centre of mass kinematics of the hammer and thrower during different hammer-throwing drills utilised for training - Gesser, T. B.; Flanagan, S. P.; Vrongistinos, K.; Whiting, W. C. (Sports Biomechanics, 2024)
During elite-level hammer throws, the vertical displacement of the centre of mass (COM) of the thrower and hammer are approximately 180° out of phase (the hammer's COM is at its high point when the thrower's COM is at its low point, and vice versa) prior to the hammer's release. This out-of-phase coordination pattern contributes to the velocity of the hammer, which ultimately contributes to the distance thrown. Several drills are used to improve coordination between the thrower's and hammer's COM, but it is not currently known if the out-of-phase pattern is present during these drills. This study examined the relative phase between the COM of the hammer and thrower during two different rotational drills: The Double Hammer Head and Single Arm drills. Using a 12-camera motion analysis system, COM kinematics for both the hammer and thrower were examined for seven NCAA Division I throwers during the two drills. Contrary to their purported purpose, the phase angles between thrower's and hammer's COM were significantly different from 180° during both drills. Further research should be conducted to examine the mechanical factors of hammer throwing drills, as well as the effect such drills have when implemented within training programs.